Different presentations of intraretinal fluid collections in optic disc pits: OCT study of 3 cases - Brasil,Oswaldo Ferreira Moura (2006)
The congenital optic disc pit is a rare anomaly that can lead to major visual impairment associated with subretinal fluid accumulation. The authors describe the optical coherence tomography study of three cases of untreated congenital optic disc pits with different levels of visual impairment and its different presentations of intraretinal fluid collections.